Hubungan Kejadian Kehamilan yang Tidak Direncanakan dengan Peran Ibu - Marlin, Riska; Yuniza, Yuniza; Rafika, Rafika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the relationship between the incidence of unplanned pregnancies and the role of mothers in the Plaju Health Center. This research was conducted using quantitative methods. The sampling technique was simple random with a total of 32 respondents at the Plaju Palembang Health Center. The results of the study showed that 13 respondents (40.6%) out of 32 respondents did not play a role and 19 respondents (59.4)% played a role. Based on the results of the statistical test using the Chi Squere test obtained a p velue value of 0.002 (p velue < 0.05), it is concluded that there is a relationship between KTD and the role of mothers. Keywords: Pregnancy, Unexpected Events (KTD), The Role of the Mother